Regulatory Administration: An Evolving and Neglected Area of Public Administration in India. (December 2018) - Sapru, Yudhishthira; Sapru, R.K.
In the current phase of liberalisation, privatisation and globalisation, and now broadly governance, regulatory administration has acquired growing importance as an instrument of achieving socio-economic objectives. It is through instrumentality of regulatory administration that the government is able to exercise effective political and economic sovereignty and control over the country's governance process and resources. Governments of nearly all developing countries have initiated policies and procedures to promote and strengthen regulatory bodies and agencies. However, the results of these promotional and regular activities have varied considerably, often reflecting large inadequacies in policies, organisational structures and procedures. Increasing emphasis is now being placed at the national level on a more flexible regulatory administration to enforce compliance with nationally established policies and requirements in various political, economic and social spheres. As a watchdog for the public interest, governments both at central and state levels should engage in activities for the promotion of social and economic justice, so as to ensure the happiness and prosperity of the people.